Metric Goodness of the Adult Prosocialness Scale. Comparative Study of Italy and Spain. (30th July 2018) - Martínez-Pampliega, Ana; Cormenzana, Susana; Sanz, Mireia; Barni, Daniela; Simon, Jordi; Alomar, Elisabeth; Pérez, Carles
Abstract: The main goal of the study is to analyze the metric goodness of the Spanish version of the Adult Prosocialness Scale (Caprara, Steca, Zelli, & Capanna, 2005). Analysis of construct and concurrent validity in two similar samples of young adults, a Spanish sample (target of the adaptation) and an Italian sample (source language), revealed the adequacy of the Spanish version of instrument, with adequate fit of the model in the Spanish group, χ 2 (96) = 405.28, p = .001, RMSEA = .071, CFI = .94, GFI = .93, and the Italian group χ 2 (97) = 224.5, p = .001, RMSEA = .075, CFI = .91, GFI = .90. The results also replicated the adequacy of the instrument found in the Italian sample, as the configural and metric invariance was verified in both groups. Analyses of benevolent and power values related to prosociality and differences between genders supported the validity of the scale. In short, the present study confirms the adequacy and sensitivity of the instrument to study prosociality in young adults in a Spanish sample.